Pemindahan Wewenang Pengadilan Negeri Dalam Mengadili Perkara Rahasia Dagang Kepada Pengadilan Niaga - Sihombing, Miranda Claudia; Suyanto, Heru (Universitas Semarang, 2024)
This research investigates the transfer of the district court’s jurisdiction in the adjudication of trade secret cases to commercial courts. The study aims to comprehend the district courts' jurisdiction in resolving trade secret disputes and the competence of commercial courts if the authority to adjudicate trade secret disputes is granted. The necessity for this research arises from the dearth of efficacious protection of trade secrets in the litigation context. The protracted duration and intricate process inherent to the current system have the potential to impede the advancement of the Indonesian economic industry, as rights holders may be dissuaded from pursuing their cases in the district court. This research employs a normative juridical approach, with a particular emphasis on the analysis of juridical norms and positive legal rules. This research builds upon previous studies that have examined the settlement of trade secret disputes in general in court and through alternative non-litigation channels. It delves deeper into the authority of the district court, comparing it with that of the United States and the Netherlands, and analyses trade secret cases that have been handled by the district court. This research indicates that the authority of the district court in trying trade secret cases requires expansion, particularly concerning closed trials. Furthermore, it can be posited that the commercial court possesses greater competence than the district court in hearing trade secret disputes, particularly in terms of more effective legal representation and more qualified judicial expertise. Penelitian ini mengkaji tentang pemindahan wewenang pengadilan negeri dalam mengadili perkara rahasia dagang kepada pengadilan niaga. Tujuan penelitian ini ialah guna memahami kewenangan pengadilan negeri dalam mengadili sengketa rahasia dagang, serta guna memahami kompetensi pengadilan niaga jika wewenang mengadili sengketa rahasia dagang diberikan. Adapun urgensi dari penelitian ini adalah kurang optimalnya perlindungan rahasia dagang dalam penyelesaian sengketa di jalur pengadilan karena durasi yang terlalu lama dan proses yang rumit, yang tentunya akan berdampak pada kemajuan industri ekonomi Indonesia karena tidak didapatnya kepercayaan para pemilik hak untuk menyelesaikan perkaranya di pengadilan negeri. Penelitian ini menggunakan pendekatan yuridis normatif yang berfokus untuk analisis menggunakan norma yuridis dan kaidah hukum positif. Penelitian ini melengkapi penelitian sebelumnya, yang hanya meninjau terkait penyelesaian sengketa rahasia dagang secara umum di pengadilan dan melalui jalur alternatif non-litigasi, dengan menganalisis lebih dalam terkait kewenangan dari pengadilan negeri, membandingkannya dengan negara Amerika dan Belanda, serta menganalisis perkara rahasia dagang yang pernah ditangani pengadilan negeri. Melalui penelitian ini, dapat dinyatakan bahwa kewenangan pengadilan negeri dalam mengadili perkara rahasia dagang perlu diperluas, terutama terkait persidangan tertutup, serta dapat dinyatakan bahwa pengadilan niaga memiliki kompetensi lebih baik daripada pengadilan negeri jika wewenang mengadili sengketa rahasia dagang diberikan, baik dari segi beracara yang lebih efektif dan kompetensi hakim yang lebih mumpuni.